2018
DOI: 10.1182/blood-2018-04-843771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spliceosome mutations on RNA splicing in myelodysplasia: dysregulated genes/pathways and clinical associations

Abstract: , , and are the most frequently mutated splicing factor genes in the myelodysplastic syndromes (MDS). We have performed a comprehensive and systematic analysis to determine the effect of these commonly mutated splicing factors on pre-mRNA splicing in the bone marrow stem/progenitor cells and in the erythroid and myeloid precursors in splicing factor mutant MDS. Using RNA-seq, we determined the aberrantly spliced genes and dysregulated pathways in CD34 cells of 84 patients with MDS. Splicing factor mutations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
221
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 200 publications
(266 citation statements)
references
References 105 publications
18
221
3
3
Order By: Relevance
“…39 30 Liang et al also observed that the SRSF2 P95H mutation affected splicing of several members of the hnRNP and SR families of proteins. Importantly, EZH2 is located at chromosome 7q36, a region frequently deleted (−7 and 7q-) in MDS.…”
Section: Mis-spliced Events In Srsf2 Del and P95h Mutated Mdsmentioning
confidence: 98%
See 1 more Smart Citation
“…39 30 Liang et al also observed that the SRSF2 P95H mutation affected splicing of several members of the hnRNP and SR families of proteins. Importantly, EZH2 is located at chromosome 7q36, a region frequently deleted (−7 and 7q-) in MDS.…”
Section: Mis-spliced Events In Srsf2 Del and P95h Mutated Mdsmentioning
confidence: 98%
“…30 More recently, splicing changes and transcriptional consequences of abnormal RNA splicing were also investigated in a large cohort of MDS samples. 30 More recently, splicing changes and transcriptional consequences of abnormal RNA splicing were also investigated in a large cohort of MDS samples.…”
Section: Mis-spliced Events In Srsf2 Del and P95h Mutated Mdsmentioning
confidence: 99%
“…In addition, the mechanistic basis of how splicing factor mutations confer selective advantage during the evolution of MDS pathogenesis remains a mystery. Although recent large‐scale transcriptomic analysis of mutations affecting SF3B1 , SRSF2 , and U2AF1 revealed global splicing dysregulation consistent with their predicted effects, there was minimal overlap between mis‐spliced transcripts altered by each of the mutant proteins . To identify key splicing abnormalities induced by mutant splicing factors, several studies provided functional evidence that expression of the abnormal splice isoforms in normal cells, or reintroduction of the canonical isoforms in spliceosomal mutant cells, can only partially phenocopy or rescue the effects of mutant spliceosome proteins .…”
Section: Effects Of Somatic Mutations In Splicing Factorsmentioning
confidence: 99%
“…These findings suggest that the pathological effects of spliceosome mutations are imparted through multiple mis‐spliced products simultaneously. In parallel, pathway analyses followed by functional validation revealed that splicing factor mutations distinctly converge on key cellular pathways to drive disease pathogenesis, including defects in DNA damage response and aberrant innate immune signaling . Further studies will be required to systematically address these fundamental questions, and more importantly, to identify the key players and pathways that can potentially be exploited for therapeutic purposes.…”
Section: Effects Of Somatic Mutations In Splicing Factorsmentioning
confidence: 99%
See 1 more Smart Citation